Life-threatening bradyarrhythmia with oral phenytoin overdose - Srinivasan, Giridharan (J Pharmacol Pharmacother, 2015)
We report a case of a 41-year-old lady, who developed severe hypotension and sinus bradycardia, following oral consumption of 20 g of phenytoin and 500 mg of glibenclamide. She required high dose of inotropes and a temporary transvenous pacer for her hemodynamic instability. This life-threatening cardiotoxicity of phenytoin could have been due to its interaction with sulphonylurea. It is imperative to be aware of drug interactions, due to which, life-threatening cardiovascular manifestations following phenytoin toxicity can occur.